INVESTIGATION ON APPLICATION OF SYNTHETIC NUTRIENTS FOR AUGMENTING WORM GROWTH RATE IN VERMICOMPOSTING - Senthilkumar Palaniappan (Journal of Urban and Environmental Engineering, 2012)
An investigation was carried out to scan the influence of synthetic nutrients on Vermicomposting. A mixture of six nutrients (Iron, Manganese, Zinc, Copper, Molybdenum and Boron) was introduced to augment the growth of worms (Lumbricus rubellus) and to ensure the higher digestion rate of the pre-composted bio-degradable organic waste. Initially green waste was collected from the local vegetable market and pre-composted for about three weeks. Then the pre-composted waste was placed in two identical glass vermireactors. Each reactor was loaded with equal volume of waste (0.024 m³) and worms (40 gm). The pre-composted waste was vermicomposted for a period of 21 days by applying nutrients in one reactor and the other was kept as control (without nutrient). The nutrients were applied in liquid form while moistening the reactor beds and the characteristics of the pre-composted waste, vermicasts and vermi growth rate were studied. Results revealed that the reactor added by nutrients performed better by achieving 41.34% higher waste volume reduction and 42% increase in the worm growth rate.